NB-DEVS: a hybrid approach for modelling and simulation of imperfect systems. (8th November 2019) - Mostefaoui, Kadda; Dahmani, Youcef
This article presents the NB-DEVS approach for the modelling and simulation of discrete event systems (DES), our objectives are to propose a new formal approach for describing the complex systems involving imperfectly. In our research we propose to integrate the naïve Bayesian network (NB) into DEVS formalism. The association of these two formalisms we have allow to extend the classic DEVS formalism to new domains. This new approach permits to study the system when its behaviour is uncertain. Finally, we simulated the evolution of the production system using our NB-DEVS approach. In simulation, we used several different models to replicate the empirical data. From these simulation iterations, we were able to verify and validate our model.